KAJIAN EVALUASI PERILAKU WISATAWAN PADA PERMUKIMAN KAMPUNG BIRU AREMA (KBA) DENGAN PENDEKATAN LANSKAP BERKELANJUTAN UNTUK KESEHATAN LINGKUNGAN - Irawan Setyabudi; Desi Kurnia; Rizki Alfian; Wahidyanti Rahayu Hastutiningtyas (BUANA SAINS, 2020)
Riverbank settlements tend to have slum environments found in urban areas. Many factors such as land use change, increasing demand, population growth urges the use of urban space as residential land. Currently in the city of Malang; as a research location; has many settlements on the banks of the river, such as along the Brantas river, namely in Betek, around Tarekot (city recreation park) and Jodipan. Many efforts from the government to change the values and perceptions of the community to have a positive connotation, with thematic village programs. This relationship is reciprocity and formed the concept of tourist villages, such as the Kampung Warna Warni and the Kampung Biru Arema (KBA). This village has an identity which has the blue nuance as an icon of the Arema football club. This village successfully built the economy of the local population but also left a negative footprint on the environment. For example, visitor behavior that does not dispose of trash in its place or a mismatch of planning applications to visitor behavior. Its influence certainly has an impact on the environmental health of the KBA community itself. This study aims to determine the pattern of visitor behavior towards KBA locations and environmental conservation efforts. The study was conducted qualitatively with the behavior mapping method and time budget, and associated with the concept of sustainable landscapes for environmental health. The results of this study are recommendations for the use of environmentally responsive open space in accordance with the behavior of visitors to tourist attractions.